Etablierung und Evaluation einer multinationalen Wissenschaftsakademie: ein neues Modell zur Stärkung des wissenschaftlichen Nachwuchses in der mikrochirurgischen Forschung - ein Konsensus Papier der DAM = Establishing and evaluating a multinational Science Academy : a new tool for fostering scientific young talents in microsurgical research - a consensus statement of the DAM - Horch, Raymund; Kengelbach-Weigand, A.; Pierer, G.; Kneser, Ulrich; Schaefer, D.; Boos, A. M.; Arkudas, Andreas; Schmidt, Volker-Jürgen (Handchirurgie, Mikrochirurgie, plastische Chirurgie, 2020)
BACKGROUND: The formation of professional networks and cooperations - in addition to any qualified good education - seems fundamental for a successful career. In a number of disciplines, various symposia or conferences exist. In the field of microsurgery, however, a specific, guided and designated opportunity for junior scientists to network with one another has been missing so far. METHODS: In 2017, a science academy was initiated for the first time by the German-speaking Association for Nerves and Vessels (DAM) with the goal of bringing together and networking microsurgically researching young physicians and scientists. This was intended to happen on a small scale once a year in order to develop synergies for joint research projects. For this purpose, motivated junior researchers were individually selected by their mentors and sent to the academy by the boards of research institutions that are organized in the DAM. After getting to know each other in a relaxed atmosphere, the participants were given the opportunity to present their respective research project within the framework of thematic blocks and moderated by experienced mentors. Each presentation was followed by a round table discussion and small group work, in which knowledge and methods were exchanged and points of contact for possible later cooperation were identified. RESULTS: In the past 3 years, the DAM Science Academy proved to be an optimal format to initiate and promote networks of young researchers comprising microsurgically interested physicians and scientists. There were many lively and in-depth discussions, which were mainly due to the open working atmosphere and the obligation to confidentiality. Most of the synergies were shown i. a. in the field of angiogenesis, bioreactor, carcinoma-ADSC interactions, stem cells, AV loop model, ischemia/reperfusion, and nerve regeneration. The participants consistently gave a very positive feedback in the final evaluation with the wish to continue this academy. CONCLUSION: The DAM Science Academy can be considered a highly suitable complemental platform to the existing networking opportunities among microsurgical researchers. Experience so far suggests that this will hopefully result in long-term cooperations and a permanent transfer of knowledge among the participants.